The SXP instrument at the European XFEL. Issue 1 (1st December 2022) - Grychtol, P.; Kohlstrunk, N.; Buck, J.; Thiess, S.; Vardanyan, V.; Doblas-Jimenez, D.; Ohnesorge, J.; Babenkov, S.; Dommach, M.; La Civita, D.; Vannoni, M.; Rossnagel, K.; et al.
Abstract: The successful implementation of the baseline instruments at the European XFEL has triggered a second phase of instrument developments aiming to extend the portfolio of available techniques. At the soft X-ray undulator (SASE 3), the Soft X-ray Port (SXP) instrument is currently under construction. Conceived as an open port, it focuses primarily on femtosecond time-resolved X-ray photoelectron spectroscopy (TR-XPES), which has proven to be a powerful tool to understand the properties of materials and the interaction between their internal degrees of freedom. The extension of this technique to the soft X-ray energy range is only possible at MHz free electron lasers (FELs) due to space-charge effects which limit the maximum photon flux per pulse on the sample. In this contribution, the SXP instrument at the European XFEL and the implementation of TR-XPES using a momentum microscope are presented. The photon energy range available at SASE 3, 0.25 keV to 3.5 keV, and the variable polarization will allow for the simultaneous characterization of the electronic, magnetic, chemical and structural properties of materials with femtosecond time resolution. To this end, a wide range of laser excitation wavelengths, ranging from the XUV to the THz region, will be available.